Molecular Cloning, Sequencing, and Characterization of a Putative Acetyl-CoA-C-acetyltransferase cDNA from a Highly Fragrant Orchid Hybrid Vanda Mimi Palmer. (19th June 2012) - Teh, Seow-Ling; Ong Abdullah, Janna; Namasivayam, Parameswari
Abstract : Vanda Mimi Palmer, a hybrid of Vanda Tan Chay Yan and Vanda tessellata (Roxb.) Hk. f . ex G. Don, is cultivated as a potted ornamental plant mainly for its fragrance rather than its look. Plant acetyl-CoA-C-acetyltransferase (ACA) is involved in the condensation of two acetyl-CoAs to form acetoacetyl-CoA, which condenses with another acetyl-CoA to yield a crucial molecule, 3-hydroxyl-3-methylglutaryl-CoA, at the initial step of the mevalonate (MVA) pathway. An ACA gene from vandaceous orchid has never been reported. We describe the isolation and molecular characterization of an ACA-like gene from V . Mimi Palmer (designated as VMPACA ) to facilitate a better understanding of the terpenoid biosynthesis pathway in orchids. The deduced VMPACA encodes a 376-amino-acid protein with a molecular weight of 39 kDa, which comprises an open reading frame of 1128 bp. It is flanked by 87 bp of 5′-untranslated region and 174 bp of 3′-untranslated region including a poly-A tail. Its protein sequence is 81% identical to other plant ACAs and contains a thiolase active site. The fluctuation expression pattern of VMPACA transcript by real-time RT-PCR showed that it is developmentally and temporally regulated with predominant expression in outer and lateral inner tepals compared to vegetative tissues.